1996
DOI: 10.1177/107110079601701104
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Shoe Gear on Human Tibial Strains Recorded During Dynamic Loading: A Pilot Study

Abstract: The study was conducted to test the hypothesis that alterations in shoe gear can affect tibial strains in the human during dynamic loading. Rosette strain gauges were mounted on the medial border of the mid-diaphysis in two human subjects with a new strain gauge bonding technique using methyl methacrylate. Strain measurements were made at this site, the most frequent location for stress fractures in the Israeli Army during treadmill walking and free running while wearing various sport shoes (Rockport ProWalker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…With respect to running, the reported compressive and tensile strains in all the studies were in range of 417-2456 me, which is maintained well below the pathological overload zone defined by the mechanostat theory. However this is unlikely in the case for shear strains where Milgrom et al (2000a,b,c) reported shear strains values measured during running between 5027 and 5533 me, which fall in the Milgrom et al (1996) Medial Rolf et al (1997) Antero and postero medial tibial mid and distal shaft cortex, respectively.…”
Section: Medial Tibiamentioning
confidence: 92%
See 2 more Smart Citations
“…With respect to running, the reported compressive and tensile strains in all the studies were in range of 417-2456 me, which is maintained well below the pathological overload zone defined by the mechanostat theory. However this is unlikely in the case for shear strains where Milgrom et al (2000a,b,c) reported shear strains values measured during running between 5027 and 5533 me, which fall in the Milgrom et al (1996) Medial Rolf et al (1997) Antero and postero medial tibial mid and distal shaft cortex, respectively.…”
Section: Medial Tibiamentioning
confidence: 92%
“…Moreover, it is not clear whether running maintains or increases bone strength. This is due to the fact that among the studies, which measured tibial strains during running, five studies (Lanyon et al, 1975;Burr et al, 1996;Milgrom et al, 1996Milgrom et al, , 2002Ekenman et al, 1998) reported strain magnitudes between 277 and 1583 me all of which fall in the physiological loading zone. Playing basketball decreased tibial stress fracture risk in infantry recruits who played basketball regularly for at least 2 years before basic training (Milgrom et al, 2000c).…”
Section: Age (Years)mentioning
confidence: 95%
See 1 more Smart Citation
“…However, the basis used for studying the stimulatory effects of mechanical strain on bone cell biological responses in vitro has been the direct measurement of bone strain in humans during various physical activities Milgrom et al, 1996;Hoshaw et al, 1997;Milgrom et al, 2004). The limitation of applying this strain magnitude data to cells in vitro, however, is that the in vivo strain gage measurements represent continuum measures of bone deformation.…”
Section: Introductionmentioning
confidence: 99%
“…This strain gauge implantation procedure typically lasted approximately 1 hour, but the strain gauge was typically attached for up to 3 days for data collection (147,148). In order to improve strain gauge bonding to the bone, the bone surface was sometimes degreased with alcohol or scored with a bone punch (148,149).…”
Section: Direct Strain Gauge Attachmentmentioning
confidence: 99%